The effort in reducing flooding by polder system, the case of East Sunter area, Jakarta - Rahardjo, Adam Pamudji; Legono, Djoko; Harsanto, Puji (2010)
Since the rapid growing of some cities in the low-land areas along the North coast of Java, more areas are needed for the expansion of the economic activites such as industries, hal/sing and other supporting uses. Nowdays, the utilization of such areas has exceeded the drainage capacity of the natural or man made canals, therefore, it needs for drainage technology to reduce the severe inundation that comes every year. This paper presents the study for expanding pump-polder system to shorten the period and to lower the inundation in the East Sunter areas in the North-East of Jakarta. The West Sunter area is already served by the Kelapa Gading drainage system that utilizes several pumps and canal networks. At some places the network connects to the old Kali Sunter. In the time being, the East Sunter is served by the old river Kali Sunter and Cakung Drain (a 100 m wide drainage canal) that carries the water to the Jakarta Bay. The old Kali Sunter flows into Cakung Drain at the downstream reach controled by a gate. The system is no longer effective to drain the severe inundation on the area. Two polders are proposed for temporary collecting the run-off effectively from the drainage sub-areas before pumped to the Drain. These polder must be able to depress the water surface on the area as soon as possible by gravity, therefore, the water surface in the polders must be controlled always sufficiently low when needed. Moreover, the micro drainage canals are also must be able to convey the run-off to the polders. The old Kali Sunter is also proposed to be normalized along some reaches. By this means the old Kali Sunter will be set as another polder and canal at the same time. As a polder, the junction to the Cakung Drain at the downstream end needs to be closed and the water is pumped up to the Drain in order to keep the water surface in the old Kali Sunter low enough. Some hydrodynamic simulations were carried out to evaluate some scenarios of the system operation and the needed capacity of the pumps and the canals.